2019
DOI: 10.5430/ijba.v10n2p129
|View full text |Cite
|
Sign up to set email alerts
|

Packaging Features Effecting on Milk Buying Behavior in Karachi

Abstract: This paper examined the packaging features effecting milk buying behavior. Four packaging features were selected that included nutritional information, price, country of origin, & quality standards, and their impact on milk consumption and purchase behavior is analyzed using Structural Equation Modeling. The study was carried out in urban areas of Karachi, among 318 respondents using Likert scale based questionnaire. The findings suggested that all four packaging features have a significant positive impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When it comes to dairy goods, variables like the atmosphere of the vending point, reachability, cleanliness, and quality have a big role in buying intention and choice (Kurajdova & Táborecka-Petrovicova, 2015). Consumers in Malaysia are steady with safety, nutrition content, and quality (Khan & Siddiqui, 2019;Rezai et al, 2011). Additionally, studies have consistently indicated that product quality has a large and beneficial influence on a buyer's purchase intention (Mirabi et al, 2015).…”
Section: Poor Product Qualitymentioning
confidence: 99%
“…When it comes to dairy goods, variables like the atmosphere of the vending point, reachability, cleanliness, and quality have a big role in buying intention and choice (Kurajdova & Táborecka-Petrovicova, 2015). Consumers in Malaysia are steady with safety, nutrition content, and quality (Khan & Siddiqui, 2019;Rezai et al, 2011). Additionally, studies have consistently indicated that product quality has a large and beneficial influence on a buyer's purchase intention (Mirabi et al, 2015).…”
Section: Poor Product Qualitymentioning
confidence: 99%
“…Khan and Siddiqui [6] observed that, consumer prefer to look into every factor before buying milk with adequate labelling and enough amount of information provided on the packaging of the dairy product more especially when it comes to high involvement product category includes health care products and daily consumable items. Moreover, country of origin and prices also plays crucial role in consumer buying pattern.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parmar and Misra [7] has mentioned in the article that, to understand the challenges faced by the dairy cooperatives during the lockdown, Verghese Kurien Centre of Excellence (VKCoE) at IRMA conducted a study on the effect of Covid-19 on the dairy cooperative sector of Gujarat. The respondents of the survey were Banaskantha District Co-operative Milk Producers' Union Ltd and Rajkot District Co-Operative Milk Producers' Union Ltd. As per the survey findings, milk procurement at village cooperative societies witnessed an increase.…”
Section: Literature Reviewmentioning
confidence: 99%